Vacuum‐Assisted Growth of Low‐Bandgap Thin Films (FA0.8MA0.2Sn0.5Pb0.5I3) for All‐Perovskite Tandem Solar Cells. Issue 5 (13th December 2019) - Abdollahi Nejand, Bahram; Hossain, Ihteaz M.; Jakoby, Marius; Moghadamzadeh, Somayeh; Abzieher, Tobias; Gharibzadeh, Saba; Schwenzer, Jonas A.; Nazari, Pariya; Schackmar, Fabian; Hauschild, Dirk; Weinhardt, Lothar; Lemmer, Uli; et al.
Abstract: All‐perovskite multijunction photovoltaics, combining a wide‐bandgap (WBG) perovskite top solar cell ( E G ≈1.6–1.8 eV) with a low‐bandgap (LBG) perovskite bottom solar cell ( E G < 1.3 eV), promise power conversion efficiencies (PCEs) >33%. While the research on WBG perovskite solar cells has advanced rapidly over the past decade, LBG perovskite solar cells lack PCE as well as stability. In this work, vacuum‐assisted growth control (VAGC) of solution‐processed LBG perovskite thin films based on mixed Sn–Pb perovskite compositions is reported. The reported perovskite thin films processed by VAGC exhibit large columnar crystals. Compared to the well‐established processing of LBG perovskites via antisolvent deposition, the VAGC approach results in a significantly enhanced charge‐carrier lifetime. The improved optoelectronic characteristics enable high‐performance LBG perovskite solar cells (1.27 eV) with PCEs up to 18.2% as well as very efficient four‐terminal all‐perovskite tandem solar cells with PCEs up to 23%. Moreover, VAGC leads to promising reproducibility and potential in the fabrication of larger active‐area solar cells up to 1 cm 2 . Abstract : Vacuum‐assisted growth control (VAGC) allows growing micrometer‐sized and pinhole‐free low‐bandgap ( E G ≈1.27 eV) perovskite thin films. VAGC exhibits promising reproducibility and potential in fabrication of larger active‐area solar cells up to 1 cm 2 . The efficient low‐bandgap perovskite solar cells fabricated by VAGC enable efficient four‐terminal all‐perovskite tandem solar cells with power conversion efficiencies up to 23%.